Factors that influence Zambian higher education lecturer's attitude towards integrating ICTs in teaching and research - Douglas Kunda; Christopher Chembe; George Mukupa (OmniaScience, 2018)
This paper investigates factors that influence Zambian higher education lecturer's attitude towards integrating ICTs in research and teaching. To determine these factors, we used online administered survey with a total of 163 respondents from public and private higher education institutions in Zambia. Quantitative data analysis based on descriptive and inferential statistics was used in this study. Inferential analysis was employed to investigate the relationships among variables using Pearson correlation analysis and completely randomized design. The results revealed that lack of adequate Internet bandwidth is among the major barrier or obstacle for assimilating ICTs in research and teaching for Zambian higher education lecturers. Additionally, training lecturers on the use of ICTs e.g. email, PowerPoint presentations, electronic boards and its advantages is the most important incentive to motivate lecturers to incorporate ICTs in research and teaching. Therefore, this study contributes to literature on factors that influence higher education lecturers' attitude towards integrating ICTs in research and teaching. This study also demonstrates a positive correlation between the important factors that influence lecturers in integrating ICTs in research and teaching.